Sistem Monitoring Horizontal Axial Wind Turbine (HAWT) Berbasis Internet Of Things - Munir Azhari; Dean Corio (Teknik Elektro Politeknik Negeri Padang, 2022)
Wind power is one of the renewable energy sources used to generate electrical energy and is generally implemented in areas with large wind potential sources. The monitoring process of the power plant is usually carried out by the operator or user by recording the current, voltage, power, and wind speed produced by the wind turbine manually or conventionally. This direct monitoring process requires greater effort and takes a long time and the data obtained is less accurate. Therefore, a monitoring system is needed that is capable of remote monitoring and applies the concept of the Internet of Things (IoT) so that the current, voltage, power, and wind speed values ​​can be obtained by users in real time through a prototype website designed. Some of the tests carried out in this study were testing the accuracy of sensor readings by looking for error values, sending data by looking for delay values, and user experience when using the website using the User Experience Questions (UEQ) method. The results showed that the monitoring system was able to provide information to users through the website with an average response time of 12.60 seconds, error in current readings of 3.51% and voltage of 0.22%. Then for the UEQ score, the website obtained a score above the average on the aspects of clarity, attractiveness, novelty, efficiency, accuracy and got a good score on the stimulation aspect.